White Matter Alterations in Depressive Disorder - He, Enling; Liu, Min; Gong, Sizhu; Fu, Xiyao; Han, Yue; Deng, Fang (Frontiers in Immunology, 2022)
Depressive disorder is currently the most common affective disorder. Studies have shown that depression is related to white matter changes. The possible mechanisms of white matter changes in depression include compromised cerebral blood flow regulation, impaired blood-brain barrier, inflammation, genetics, and environment. The white matter changes in patients with depression are related to many clinical factors such as differential diagnosis, its severity, treatment effect, and efficacy evaluation. This article reviews the characteristics, possible mechanisms, and clinical relationships of white matter alterations caused by depressive disorder.